Rural resilience and the role of social capital among farmers in Kirundo province, Northern Burundi - Minani, Bonaventure; Rurema, Déo-Guide; Lebailly, Philippe (Applied Studies in Agribusiness and Commerce, 2013)
In Burundi, more than 90% of the active population is engaged in family agriculture, which plays a vital role in food production and constitutes more than 50% of the GDP. Before the civil war of 1993, Kirundo was deemed the “breadbasket of the country”, as the region fed many parts of Burundi through growing particular foods such as legumes and cereals. Family farming was market-oriented. Kirundo alone includes 8 lakes which offer opportunities for field irrigation. Today, this region is the first province in Burundi which shows a high rate of malnutrition, as poverty has increased and a sharp 53.9 % decline in agricultural production has been witnessed between 1996 and 2009. The aim of this article is to analyse the role of social capital through the local association network in improving family agriculture and the resilience to climate change and conflict crisis. In this study, 73 farmers were surveyed in Kirundo province through means of a questionnaire, and the study was completed by collecting secondary data. Analysis of the data reveals that, despite recurrent droughts in that region which caused deaths due to famines and displacement of people to neighbouring countries such as Rwanda and Tanzania, 44% of the farmers who were surveyed were shown to have resilience to climate change. The analysis of data shows that these farmers were members of well organised local associations, and had learned about specific topics such as financial management, processing and storage of agricultural products and livestock. The social capital network positively influences their income and their resilience to climate change and conflict crisis.